PENERAPAN MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION (AIR) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS XI IPS DI SMA NEGERI 2 PEKANBARU - Endah Septiana, Patricia; Bunari, Bunari; Al-Fiqri, Yanuar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The results of observations at SMA Negeri 2 Pekanbaru show that student learning outcomes are not optimal. This study uses a Cooperative learning model, namely Auditory Intellectually Repetition (AIR) to improve student learning outcomes in history learning. The purpose of the learning model is an effective approach to improve student learning outcomes, helping students understand the material in depth and remember it in the long term. The type of research is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of 4 stages, namely: planning, implementation, observation, and reflection. The results of this study indicate that 1) teacher activity in cycle I obtained an average of 60.00% with the criteria of